2014
DOI: 10.1002/tox.22025
|View full text |Cite
|
Sign up to set email alerts
|

Silica‐carrying particulate matter enhances Bjerkandera adusta‐induced murine lung eosinophilia

Abstract: Bjerkandera adusta (B. adusta) causes fungus-associated chronic cough. However, the inflammatory response is not yet fully understood. Recently, B. adusta was identified in Asian sand dust (ASD) aerosol. This study investigated the enhancing effects of ASD on B. adusta-induced lung inflammation. B. adusta was inactivated by formalin. ASD was heated to remove toxic organic substances. ICR mice were intratracheally instilled with saline, B. adusta 0.2 µg, or B. adusta 0.8 µg with or without heated ASD 0.1 mg (H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Mechanisms There are many examples and potential mechanisms by which occupational and environmental factors may cause or exacerbate an acute or chronic cough, as summarized in Table 1. Direct effects of particulates or gas may be to stimulate cough receptors or directly induce asthma, [4][5][6] and it is possible that direct effects of noxious chemicals such as ammonia, through trigeminal nerve stimulation, may increase awareness of the sensation (although this relation specifically to cough has not been substantiated). 7 Indirect effects of occupational dust and allergens are strongly associated with secondary infectious or noninfectious sinusitis, bronchitis, and cough-variant asthma, with stimulation of the cough triggered by inflammatory mediators or by direct neurogenic stimulation.…”
Section: Background Informationmentioning
confidence: 99%
“…Mechanisms There are many examples and potential mechanisms by which occupational and environmental factors may cause or exacerbate an acute or chronic cough, as summarized in Table 1. Direct effects of particulates or gas may be to stimulate cough receptors or directly induce asthma, [4][5][6] and it is possible that direct effects of noxious chemicals such as ammonia, through trigeminal nerve stimulation, may increase awareness of the sensation (although this relation specifically to cough has not been substantiated). 7 Indirect effects of occupational dust and allergens are strongly associated with secondary infectious or noninfectious sinusitis, bronchitis, and cough-variant asthma, with stimulation of the cough triggered by inflammatory mediators or by direct neurogenic stimulation.…”
Section: Background Informationmentioning
confidence: 99%
“…In accordance with these clinical studies, our recent experimental research showed that B. adusta alone caused an eosinophil-rich pulmonary inflammatory response and Th2 cytokine [such as interleukin (IL)-5] production in mice, as well as increased inflammatory molecule secretion from bone marrow-derived macrophages (BMDM) in vitro [12]. We also found that B. adusta caused eosinophilic airway inflammation and aggravated ovalbumin-induced murine lung eosinophilia along with fibrous thickening of the subepithelial layer [13].…”
Section: Introductionmentioning
confidence: 66%
“…WT, TLR2 -/- , TLR4 -/- , TLR2/4 -/- , TLR7/9 -/- , and MyD88 -/- mice (on a C57BL/6J background, n = 4/genotype) were purchased from Oriental Bioservice [12]. Femurs were removed at 8 weeks of age, and soft tissue was removed and flushed with Hanks' solution to recover the bone marrow.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TLR4 ligand lipopolysaccharide (LPS) and TLR2 ligands such as β-glucan are strong candidates for causing the exacerbation of lung eosinophilia by ASD [ 21 ]. An in vitro study showed that TLR2 rather than TLR4 contributes to the production of pro-inflammatory cytokines from bone marrow-derived macrophages [ 23 ]. On the basis of these results, we speculated that ASD-adherent β-glucan is one of the exacerbating factors of lung eosinophilia.…”
Section: Introductionmentioning
confidence: 99%